The Characteristic of adapting the system of administrative Islamic thought in the era - Idrees Qadeer hamdameen (QALAAI ZANIST JOURNAL, 2024)
The Characteristics of adapting the system of administrative Islamic thought of the era is considered the most important subject of the Political Field and society of the era, so it is separated from all messages and system, Whether religions or artificial. It is a divine system and its basic source is inspiration of Allah and the prophet’s words. (Peace be upon him). It is a system that combines religion and state together cares about human and spiritual factors, and joins human beings in administrative Works and respect it and proves that no nation can live and build civilization if everything is not stable and cannot live if everything is changed. From this point of view both researchers talk about the important of Islamic belief and ack now edging God and god’s oneness, talk about the important of a detailed balanced in the changes and un changes in Islamic decisions and guidelines. So, it reviews briefly about the characteristics of adeptly the system of administrative Islamic thought of the era. Their research consists of three themes, the first axis of belief system, the second axis of the religious system, the third axis of stability of the principles and the change of shapes.